The Effect of Liquid Suppermentary PPC (Eichornia crassipess) On Growth and Yield Of Green Spinach (Amaranthus gangeticus) - Agus Miftakhurrohmat; Nion Yen (Nabatia, 2019)
The purpose of this study was to determine the effect of the treatment of supplemen- tary liquid hyacinth fertilizer on the character of growth and production of green spinach plants. This research was carried out in Keboan Anom Gedangan Sidoarjo Village, Octo- ber to December 2018. This study used a single randomized block design (RBD) using variance analysis a 5% BNJ test which was repeated four times with the concentration factor of PPC hyacinth goiter which consists of 6 types, namely the concentration of 0% (T0), concentration of 10% (T1), concentration of 20% (T2), concentration of 30% (T3), concentration of 40% (T4), concentration of 50% (T5). Observastion variable included plant height, number of leaves, number of branches, stem diameter, wet weight, dry weight, harvest indexs. The result showed a significant effect on the harvest indexs, sig- nificantly affected plant height, stem diameter, number of leaves, number of branches, while the wet weight showed a significant effect, and dry weight had a very significanr effect. And treament of T5 (30 ml/liter) the highhest average yield in wet weight is 10.43 grams.